Redoing the pathways of the discipline socio-anthropological bases of Physical Education - Gomes, Daniel Pinto (2021)
This experience report presents the path taken by teachers and students in the Socio-Anthropological Bases of Physical Education classes, from the 2014.2 and 2016.2 academic periods, from the Physical Education Degree course at the Canindé campus, from the Federal Institute of Education, Science and Technology of Ceará (IFCE). Highlighting the theoretical and methodological assumptions that permeated the training of students (future teachers) of Physical Education in due years and discussing the dynamics and tensions of the teaching and learning process. Aiming to provide a broader view and reflection on the pedagogical practice of that discipline. Thus, notably in the first class, greater emphasis was given to the cultural universe involved in recreational activities and physical exercise. In the second class, the teacher tried to balance, during the semester, the affinity between the sociological and anthropological debate, however it is possible to verify that the time dedicated to this discipline is still small.